Highly permselective contorted polyamide desalination membranes with enhanced free volume fabricated by mLbL assembly - Shaligram, Sayali; Shevate, Rahul; Paul, Siddhartha; Shaffer, Devin L. (ACS Applied Materials & Interfaces, 2025)
The permeability-selectivity trade-off in polymeric desalination membranes limits the efficiency and increases the costs of reverse osmosis and nanofiltration systems. Ultrathin contorted polyamide films with enhanced free volume demonstrate an impressive 8-fold increase in water permeance while maintaining equivalent salt rejection compared to conventional polyamide membranes made with m-phenylenediamine and trimesoyl chloride monomers. The solution-based molecular layer-by-layer (mLbL) deposition technique employed for membrane fabrication sequentially reacts a shape-persistent contorted diamine monomer with a trimesoyl chloride monomer, forming highly cross-linked, dense polyamide networks while avoiding the kinetic and mass transfer limitations of traditional interfacial polymerization. The mLbL process allows precise nanoscale control over polyamide selective layer thickness, network structure, and surface roughness. The resulting controlled film thicknesses enable direct measurements of water and NaCl permeabilities. The permselectivities of contorted polyamide membranes surpass those of commercial desalination membranes and approach the reported polyamide upper bound. Solution-diffusion transport modeling indicates that this high permselectivity may be attributed to enhanced water transport pathways in the contorted polyamides that increase water diffusivity-permeability while maintaining high solute rejection through solubility-selectivity.
Keywords: Desalination; molecular layer-by-layer assembly; permselectivity; polyamide; polymers of intrinsicmicroporosity; triptycene; Troger's base